Socio-economic influence on municipal solid waste generation in Petaling Jaya - P, Agamuthu,; M, Lingesveeramani,; H, Bregnhoj, (Malaysian Journal of Science, 2004)
Municipal Solid Waste (MSW) generation rate in Malaysia was found to vary according to the t\pe of waste generator, land use and economic level. Waste was collected and sorted from five types of housing area (single-storey terrace, double-storey terrace, single-storey bungalow, double-storey bungalow and condominium) in Section 11 and 12, Petaling Jaya, Selangor Darul Ehsan. Residents in single-store} bungalow generate 17.6kg/week/dwelling of MSW, followed by double-storey terrace houses at 16.3kg/week/dwelling, single-storey terrace houses produced at 10.2kg/week/dwelling, doubleÂstore} bungalow 10.2kg/week/dwelling and condominium residents generated 7.3kg/week/dwelling. Per capital generation rate which depends on waste generated and number of people in the house, shows residents in single-storey bungalow generate 0.12-0.88kg/person/day of MSW, double-storey bungalow residents (0.14-0.41kg/person/day), single-storey terrace residents (0.1 l-0.52kg/person/day), double- store} terrace residents (0.20-0.62kg/person/day), condominium residents (0.12-0.26kg/person/day) and. Physical characteristic^ of MSW also differed for the various types of housing area. MSW pH values mnged from 5.08 to 6.20. Conductivity values of MSW ranged from 83 to 969pS and moisture content of i/i'SW was from 36.59% to 76.16%. On the occupational aspect, public sector working residents generate more MSW (0.44kg/person/day) compared to private sector working residents (0.34kg/person/day) and .".indents (0.24kg/person/day). Indian residents were found to generate more MSW, at 0.35kg/person/day compared to Chinese, 0.32kg/person/day while Malays generated, 0.29kg/person/day. Medium-income msidents (RM1500-RM4000) generated less MSW at 1.26kg/residence/day while high-income residents (-RM4000) generated 1.38kg/residence/day and low-income residents (<RM1500) generated, i .94-kg/residence/day. Average MSW generation rate at Section 11 and 12, Petaling Jaya was range from 0.11-0.88kg,'person/day and average waste composition are organic 42.0%, paper products 18.2%, plastics 18 7%. glass 4.3%, non-ferrous metal 3.4%, ferrous metal 0.5%, polystyrene 1.1% and others 11.8%. Socio-economic factors; housing type, occupational type, race and income level play a major role in ML â– :/ generation while educational level has a minor influence.